Mechanical Transmission of Rotational Motion between Molecular-Scale Gears - Lin, H-H; Croy, Alexander; Gutierrez, Rafael; Joachim, C.; Cuniberti, Gianaurelio (Giovanni) (Physical Review Applied, 2020)
The manipulation and coupling of molecule gears is the first step toward realizing molecular-scale mechanical machines. Here, we theoretically investigate the behavior of such gears using molecular-dynamics simulations. Within a nearly rigid-body approximation, we reduce the dynamics of the gears to the rotational motion around the orientation vector. This allows us to study their behavior based on a few collective variables. Specifically, for a single hexa(4-tert-butylphenyl)benzene molecule, we show that the rotational-angle dynamics correspond to those of a Brownian rotor. For two such coupled gears, we extract the effective interaction potential and find that it is strongly dependent on the center-of-mass distance. Finally, we study the collective motion of a train of gears. We demonstrate the existence of three different regimes, depending on the magnitude of the driving torque of the first gear: Underdriving, driving, and overdriving, which correspond, respectively, to no collective rotation, collective rotation, and only single-gear rotation. This behavior can be understood in terms of a simplified interaction potential.
CRIS-Team Scopus Importer:2022-04-14